2011
DOI: 10.1103/physrevb.83.195120
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast insulator-metal phase transition in VO2studied by multiterahertz spectroscopy

Abstract: The ultrafast photoinduced insulator-metal transition in VO 2 is studied at different temperatures and excitation fluences using multi-THz probe pulses. The spectrally resolved midinfrared response allows us to trace separately the dynamics of lattice and electronic degrees of freedom with a time resolution of 40 fs. The critical fluence of the optical pump pulse, which drives the system into a long-lived metallic state, is found to increase with decreasing temperature. Under all measurement conditions, we obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
184
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(200 citation statements)
references
References 62 publications
(95 reference statements)
15
184
1
Order By: Relevance
“…16 The metal-insulator transition can be influenced by a variety of external parameters, and recent work have considered the effects of strain [17][18][19] and lattice misfit with the substrate, 20,21 electric field or current activation, [22][23][24][25][26][27][28][29][30][31] light irradiation, [32][33][34][35][36][37][38] ion bombardment, 39,40 and gaseous ambience. 41 Considering the wealth of possibilities to modulate the properties of VO 2 -based thin films, it is not surprising that they are discussed for a vast number of applications such as thermochromic "smart" windows for energy efficient buildings, [42][43][44][45][46][47][48][49][50] variable-thermal-emittance surfaces for thermal radiation control, 51 oscillators and switches in (opto)electronics, 25,26,34,52,53 transistors of different types, 30,54,55 microcantilevers, 56,...…”
Section: Introductionmentioning
confidence: 99%
“…16 The metal-insulator transition can be influenced by a variety of external parameters, and recent work have considered the effects of strain [17][18][19] and lattice misfit with the substrate, 20,21 electric field or current activation, [22][23][24][25][26][27][28][29][30][31] light irradiation, [32][33][34][35][36][37][38] ion bombardment, 39,40 and gaseous ambience. 41 Considering the wealth of possibilities to modulate the properties of VO 2 -based thin films, it is not surprising that they are discussed for a vast number of applications such as thermochromic "smart" windows for energy efficient buildings, [42][43][44][45][46][47][48][49][50] variable-thermal-emittance surfaces for thermal radiation control, 51 oscillators and switches in (opto)electronics, 25,26,34,52,53 transistors of different types, 30,54,55 microcantilevers, 56,...…”
Section: Introductionmentioning
confidence: 99%
“…In the linear absorption regime, this fluence corresponds to exciting approximately 1 in 10 vanadium ions, and the total deposited energy is similar to the thermal energy required to drive the phase transition in equilibrium conditions. It has also been shown that, for excitation above the optical band gap, the threshold is independent of the pump wavelength 16 and only depends on the absorbed energy density and, as expected, the threshold value is reduced when the initial temperature of the sample is increased 7,9 . In addition, it has been observed that there are three distinct regimes for the photoinduced transition.…”
mentioning
confidence: 93%
“…In these time-resolved experiments, a strong pump pulse excites the system and a second pulse probes a specific property as a function of time delay. To date, the time-dependent change in the optical reflectivity and conductivity [7][8][9] as well as the electronic 10,11 and lattice [12][13][14][15] changes during the dynamic IM transition have been measured. To drive the insulator-metal transition, an incident threshold fluence, F TH , of approximately 7 mJ cm −2 has been reported when the sample is excited with 800 nm laser light at room temperature.…”
mentioning
confidence: 99%
“…[12][13][14][15] Much previous effort has been focused on understanding the physics behind the MIT, especially the role electron-electron correlation and electron-lattice coupling play in driving the simultaneous structural and electronic phase transition. [14,[16][17][18][19][20] Whether the insulating M 1…”
Section: Introductionmentioning
confidence: 99%